The role of monocytes in malaria infection - Keh Min Xuan; Nurhidanatasha Abu Bakar; Khairul Mohd Fadzli Mustaffa; Maryam Azlan (Central European Journal of Immunology, 2023)
Malaria remains one of the most common human infections worldwide. In endemic areas, malaria is a leading cause of morbidity and mortality and it imposes significant socioeconomic burdens on the people affected. Monocytes are part of the immune system controlling parasite burden and protecting the host against malaria infection. Monocytes play their protective roles against malaria via phagocytosis, cytokine production and antigen presentation. Though monocytes are crucial for clearance of malaria infection, they have also been shown to cause adverse clinical outcomes. In this review, we discuss recent findings regarding the role of monocytes in malaria via mechanisms such as parasite detection and clearance, pro-inflammatory activities, and activation of other immune components. We also highlight the role of different monocyte subsets, and other myeloid cells that are involved in malaria infection. However, more investigations are required in order to explore the exact roles of these monocytes in malaria infection.